Ecosystem services in livestock farming: Integral valuation framework and field applications - Florez, Jesus Fernando; Louhaichi, Mounir; Yigezu, Yigezu Atnafe; Abdrahmane, Wane; Hassan, Sawsan; Gonzalez Quintero, Ricardo; Notenbaert, An; Burkart, Stefan (2024)
This document presents a framework for evaluating the environmental, economic, and social dimensions of ecosystem services in livestock systems. Livestock plays a critical role in global food security and economies but also contributes to environmental challenges, including deforestation and greenhouse gas emissions. To address these issues, the Ecosystem Services Advisory Group, established under the One CGIAR Initiative on Livestock and Climate (L&C), seeks to promote sustainable livestock practices. Key ecosystem services highlighted in this framework include food and feed production, carbon sequestration, soil fertility enhancement, microclimatic regulation, biodiversity conservation, and emission reductions. The proposed integrated valuation strategy assesses ecological benefits, economic value, and social perceptions, aiming to support sustainable livestock management. Field applications in Colombia, Kenya, and Tunisia demonstrate the advantages of silvopastoral systems and improved pastures in boosting productivity, mitigating greenhouse gas emissions, and enhancing ecosystem resilience. The framework emphasizes the importance of balancing livestock production with environmental sustainability through innovative practices. Looking ahead, the initiative will focus on expanding evaluations across Latin America and Africa, refining methodologies, and strengthening stakeholder engagement to advance sustainable livestock farming on a global scale.